A cloud-based Giscience learning approach to spanish national parks - Javier ÁLVAREZ OTERO; María Luisa DE LÁZARO Y TORRES; María Jesús GONZÁLEZ GONZÁLEZ (European Journal of Geography)
GIScience learning is the main aim of the GI Learner project, which can be easily achieved using the cloud: open data online from Spatial Data Infrastructures (SDI of Spain). School on the Cloud network has promoted a cloud-based learning approach by dealing with access,sharing and reusability of cloud resources. Thus, based on the results of two European projects, the objective of the article is to focus on improving awareness of sustainability by building itineraries based on places of interest within the best protected areas in Spain, the National Parks, using SDI geoinformation. The methodology of (re)using open data online from SDI by linking cloud knowledge with real Earth and the three selected Parks for a better spatial understanding has been shown to be a very useful way to understand territory. Thus, to improve the learning of sustainable management of National Parks by using cloud computing and SDI it may well prove to be an essential part of environmental education and social responsibility.